An Unusual Cause of Cerebral Infarction in a Tanzanian School Child. (November 2022) - Lodhia, Jay; Chipongo, Hilary; Sadiq, Adnan; Khelef, Khadija; Bosco, Kenan; Dekker, Marieke
Pediatric stroke is uncommon. A traumatic cause of pediatric ischemic stroke is even rarer. Ischemic stroke due to intraluminal thrombus can be acutely treated with thrombolysis but various factors in sub-Saharan Africa make this unfeasible. We present a case of an eight-year-old Tanzanian boy who sustained penetrating trauma to his palate developing an ischemic stroke of his right middle cerebral artery territory.